Kesesuaian Kosa Kata dan Latihannya dalam Buku Tangram 1A dengan Materi Bahasa Jerman SMA - KHOFIFAH, DIAN (LATERNE, 2013)
This study reviews the presentation of vocabulary in the book Tangram 1A. Because understanding vocabulary is generally regarded as an important part of the process of learning a language or developing one's ability in a language that has been mastered. Good vocabulary presented in the textbook and in the German language conversation. In foreign language learning, the role of textbooks is very important, especially the vocabulary presented in the book. This study aims to describe and practice vocabulary in the book Tangram 1A with high school German language materials. In this study, the writer uses descriptive qualitative method. The data has been obtained, collected, classified, and analyzed based on the presentation of vocabulary and practice according to the theory which has been described in chapter II. Results of the analysis / research is: When viewed from the theme, there are 2 common theme in the book Tangram 1A with Kontakte Deutsch 1. It is assumed that the same theme, there is a new presentation of the same vocabulary as well. That is the theme of 'Self Identity and' Pastimes / Hobbies'. In the theme of 'Personal Identity' have the word Name, Wohnort, Adresse, Land, Stadt, Insel, Zahlen, heiβen, wohnen, kommen, machen, gehen, sein, gut, auch, es geht, null, eins, zwei, drei, as well as 'Redemittel' the same are: Hallo!, guten Morgen (Salam), Ihnen Wie geht's? (Asking and answering circumstances), Woher kommst du? (Asking and answering origin), Wo wohnst du? (Asking and answering residence), Wer ist das? (asking and introduce others). While the theme of 'Pastimes / Hobbies' are the same word are: Fuβball, besuchen. 'Redemittel' the same are: Wann Urlaub machen Sie? (Asking and called the day / time information). In practice there are 4 suitability vocabulary, such as: Code 1c.l, 1d.l, 2h.l, and 3j.l. Presentation of the exercises overall Tangram 1A begins with step Memory - Comprehension - Application - Memory. While the book Kontakte Deutsch theme 'Personal Identity' is the stage recollection - Application, and the theme of 'Pastimes / hobbies' are successive phases of memory - Comprehension – Application Keywords: vocabulary, Tangram 1A, Senior high school's material